Wider range of allodynia in a rat model of repeated dural nociception compared with infraorbital nerve chronic constriction injury. (14th February 2018) - Hu, Guanqun; Zhang, Mingjie; Su, Min; Zhang, Qing; Wu, Hangfei; Wang, Xiaolin; Dong, Zhao; Yu, Shengyuan
Highlights: Cephalic and extra-cephalic allodynia exist in the interictal period in IS rats. Wider range of allodynia in the IS model compared with the IoN-CCI model. IS and IoN-CCI can be seen as suitable animal models of CM and TN, respectively. Abstract: Background: To identify differences in allodynia and grooming behaviours between rat models of either repeated dural nociception with inflammatory soup (IS) or infraorbital nerve chronic constriction injury (IoN-CCI). Methods: Repeated dural nociception was induced via the application of IS to the dural meninges and IoN-CCI was applied to model neuropathic pain. All surgeries were performed on the right side and a sham operation was performed on the control group. Mechanical and thermal withdrawal thresholds were tested on different facial areas and hindpaw during the interictal period and grooming behaviours were recorded. Results: A significant decreases was found in the mechanical withdrawal thresholds of the bilateral vibrissa pad and right periorbital area in both the IS and the IoN-CCI groups, but only in the left periorbital area of the IS group. Hindpaw thermal allodynia was evident only in the IS group. Ipsilateral hindpaw grooming behaviour increased in the IS group and facial grooming behaviour increased in the IoN-CCI group. Conclusions: Repeated dural nociception induced by IS and IoN-CCI in rats effectively simulated chronic migraine (CM) and trigeminal neuralgia (TN), respectively. The IS group exhibited a wider range of allodynia than the IoN-CCI group, but further studies are necessary to determine underlying mechanisms.